The Horizontal Effect of the Free Movement Provisions - (:unkn) unknown (SAGE Publications Ltd, 2011)
The article scrutinizes the issue of horizontal effect in the field of fundamental freedoms. In that regard two main sub-issues are explored: First, the ratione materiae and ratione personae scope of horizontal direct effect of the Treaty provisions on freedom of movement for workers, freedom to provide services and freedom of establishment is examined with their main rationales. Second, in addition to indirect horizontal direct of the Treaty provisions on free movement of goods, it is examined whether horizontal direct effect in the field of free movement of goods is provided by these provisions on the basis of the same rationales, if not, by the general principle of non-discrimination on grounds of nationality of EU law. © 2011 SAGE Publications.
Keywords: competition; fundamental freedoms; horizontal direct effect; indirect horizontal effect; the general principle of nondiscrimination of EU law